Menguak Islam Eksklusif yang Toleran - Fata, Ahmad Khoirul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2011)
This paper speaks of something unusual. Exlusive Islam has been commonly branded as untolerant, while the inclusive Islam has been identified as tolerant. This paper tries to prove the reverse that the exclusive Islam can be tolerant too. It addresses first the problem of religion-based conflict in Indonesia arguing it is this problem that provoked the birth of such liberal font of Islam called Jaringan Islam Liberal (JIL). Born to propagate the polite Islam, the movement turned out to be just another defect within the Muslim society. The fact is that, majority of Muslims in the country are not happy with it. The reaction of Muslims varied, and culminated in the issuance of the Indonesian Council of Ulama (Majelis Ulama Indonesia/ MUI) that such notion as religious pluralism that the movement is busy campaigning for is forbidden religiously. This paper is an attempt to reconstruct the pluralistic discourse in a way that would not iritate the conservative segment of Muslim society. It also tries to understand why majority of Muslims in this country rejected the idea of religious pluralism propounded by the liberals.